Scutellarin Protects Against Mitochondrial Reactive Oxygen Species-Dependent NLRP3 Inflammasome Activation to Attenuate Intervertebral Disc Degeneration - Wang, Zihao; Zhang, Pengfei; Zhao, Yunpeng; Yu, Feiran; Wang, Shaoyi; Liu, Kaiwen; Cheng, Xiang; Shi, Jie; He, Qiting; Xia, Yanni; Cheng, Lei (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral disc degeneration (IVDD) is a predominant cause of disc herniation and is widespread worldwide. Inflammatory responses, mitochondrial dysfunction and extracellular matrix degradation are known to be involved in IVDD. Scutellarin, an active ingredient extracted from Erigeron breviscapus (Vaniot) Ha, Hand-Mazz, is reported to exhibit therapeutic potential in several degenerative diseases by suppressing inflammation and regulating metabolism. However, whether scutellarin can improve IVDD remains unknown. Human primary nucleus pulposus cells (HNPCs) were cultured and stimulated with TNF-α in the presence or absence of scutellarin. Furthermore, a rat needle puncture model was established, and scutellarin was injected into the IVD to verify its protective function against IVDD. Scutellarin attenuated the inflammatory reaction and retained the production of major IVD components both in vitro and in vivo. Mechanistically, scutellarin reduced the amount of reactive oxygen species (ROS), alleviated mitochondrial damage and decreased the expression levels of apoptosis-related biomarkers upon stimulation with TNF-α. In addition, scutellarin antagonized the activation of the nuclear factor κ-light-chain-enhancer of activated B (NF-κB) signalling pathway and the mitogen-activated protein kinase (MAPK) signalling pathway and suppressed the activity of the NLRP3 inflammasome mediated by TNF-α. This study reveals that scutellarin protects against degeneration of nucleus pulposus cells, which might shed light on treatment of IVDD in the future.